Smallholder Farming Households' Make-or-Buy Decisions: Linking Market Access, Production Risks, and Production Diversity to Dietary Diversity - Keenan, Michael; Karanja Ng'ang'a, Stanley; Pamuk, Haki; Ruben, Ruerd (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Production risk and market access put pressure on agricultural household production and food consumption decisions. Improving market access and promoting production diversity have been proposed as solutions to better agricultural household nutritional outcomes. Particularly with regards to production diversity, the efficacy of these solutions has been called into question. We show that the effectiveness of increased production diversity translating into improved household nutrition is dependent on levels of market participation and access. To demonstrate these results, this paper develops a non-separable agricultural household model with multiple agricultural goods for consumption and/or production, production risk, and imperfect markets. Households jointly maximize production, consumption, and marketing decisions. The model’s results are tested econometrically using nationally representative data from Tanzania. The paper contributes to a growing empirical literature concerning the relationships between production diversity, market access, and dietary diversity. We show that while on average a household needs to grow ten additional food groups to consume just one more food group, households not participating in markets need to grow just four more food groups to consume one more. This interaction explains why the literature typically finds weak correlations between dietary diversity and production diversity for typical households. The paper also contributes to the theoretical literature surrounding non-separable household models by providing a framework for understanding the role of markets and risk for household dietary diversity by developing. Our model provides economic theory consistent with existing empirical evidence and helps explain why most studies only find a small link between production diversity and dietary diversity.